Florida 4-H Treasurer's Manual and Record Book - Joy Jordan; Mary Thomas; Tiffany Browning (EDIS)
So, you’ve been elected treasurer of your 4-H club! This revised 36-page record book will help guide you in your duties and responsibilities and will be the official financial record of your club. Written by Joy Jordan and published by the UF Department of 4-H Youth Development, March 2012.